CMOS-fabricated ring surface ion trap with TSV integration - Zhao, Peng (2024)
We present the design, fabrication, and test of ring surface trap on 12-inch wafers with a CMOS process. The design is based on Through Silicon Vias (TSV) interconnects. Up to 200 ions were loaded and cooled; preliminary compensations of electrostatic potential imperfections show that rotational symmetry can be partially restored.